Effect of sprayed different concentrations of Moringa oleifera leaves extract on broiler breeder hatching eggs - Sulaiman, Bnar F. (Journal of Kerbala for Agricultural Sciences, 2023)
This research aimed to study the impact of spraying different Concentrations of Moringa oleifera leaves Extract on Broiler Breeder Hatching Eggs. The results cleared that, at 18th day the egg weight ranged from 60.50 in the group treated with 5 % M. Water extract to 62.16 gm in control group. While, the egg losses observed in group 4 that, treated with 2 % M. water extract that was 20.56 % at 21st day. The higher hatchability % of total eggs showed in control group that was 69.70 %. While, the hatchability % of fertile eggs showed a higher percentage in group 5 that treated with 5 % M. Water extract that was 99.02 %. The higher percentage of dead embryo observed in control group that was 9.10 % and the lower level observed in the group 2 that treated with 2 % M. Alchole exteract that was 5.46 %. The total aerobic bacteria counts at 18th day of incubation showed a lower level in group 5 that treated with 5 % M. water extract that was 7.88. while, the activity of chicks and in abnormal chicks increased in group that treated with 5% M. Water extract that was 8.96 % and 2 % respectively. Overall, the higher concentration of Alchole extract of M. olifera , increased the weight of hatching eggs with a reduction in total egg losses,% of the eggs. While, the higher concentration of the water extract of M. olifera improved the hatchability % a reduction in total aerobic counts on the egg shell and improved chick quality and activity.